Work and Family - Hynes, Kathryn (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
Course Description:"Balancing work and family" is one of the catch-phrases of the decade, reflecting the challenges of successfully meeting both work and family responsibilities. This course will examine the social and demographic changes that have put work and family on the policy agenda, the different strategies used to balance work and family, and the impact of those strategies on women, men, and children. We will discuss social theories about employment decisions, social change, social norms, and issues of gender and socioeconomic equality. We will conclude with a broad overview of the responses of employers and government to current work-family issues, which will be followed by an in-depth examination of parental leave policies.